Munasabah dan Urgensinya dalam Tafsir al-Qur’an - Salam, Muhammad Tohir; Ihya' Ulumudin (Moderasi : Journal of Islamic Studies, 2023)
This research focuses on munasabah, or conformity, in the al-Qur'an. This research uses qualitative methods, and data collection uses documentation. In data analysis, researchers used inductive, deductive, and descriptive analysis. Based on the research results, it can be concluded that the Ulama' are divided into two groups in responding to the application of munasabah in the al-Qur'an: those who are pro and those who are against. Pro-Secularists argue that munasabah is very helpful in understanding the Koran. Meanwhile, opposing scholars argue that the verses of the Koran have their own historical context. So, it is not appropriate for munasabah to be applied in all verses of the al-Qur'an.